Media, anthropology and public engagement - Pink, Sarah; Abram, Simone (Studies in public and applied anthropology, 2015)
Contemporary anthropology is done in a world where social and digital media are playing an increasingly significant role, where anthropological and arts practices are often intertwined in museum and public intervention contexts, and where anthropologists are encouraged to engage with mass media. Because anthropologists are often expected and inspired to ensure their work engages with public issues, these opportunities to disseminate work in new ways and to new publics simultaneously create challenges as anthropologists move their practice into unfamiliar collaborative domains and expose their research to new forms of scrutiny. In this volume, contributors question whether a fresh public anthropology is emerging through these new practices.